Train Protection Canceling and Application for Metro Signals - TANG Bin; ZHANG Datao (机车电传动)
Conditions and occasion of metro vehicles general canceling, manual and fault relieving was introduced. Combined the implementation of train protection canceling in Changsha metro line 2 under different conditions, operation safety was explained, which provided ideas for design and maintenance men.